Effects of puerarin on the intervertebral disc degeneration and biological characteristics of nucleus pulposus cells - Hengtao Tang; Song Zhang; Xinchang Lu; Tongyu Geng (Taylor & Francis Group, 2023)
AbstractContext Intervertebral disc degeneration (IDD) is the pathological basis of spinal degenerative diseases. Puerarin (PU) is an isoflavonoid with functions and medicinal properties.Objective To explore the effect of PU on IDD and its potential mechanism of action.Materials and methods Sprague-Dawley (SD) rats were divided into sham, IDD, low PU, and high PU groups. Rat nucleus pulposus cells (NPCs) were isolated and divided into control, IL-1β, 100 and 200 μmol/mL PU, TAK-242 (TLR4 inhibitor), or 200 μmol/mL PU + LPS (TLR4 activator) groups. The water content, inflammatory factors, proliferation activity, TLR4/NF-κB pathway activity, apoptosis rate, protein expression of apoptosis, and histology of the extracellular matrix (ECM) were analysed.Results In vivo: Compared with the IDD group, disorganization of intervertebral disc tissue was significantly improved, water content (2.80 ± 0.24 mg, 3.91 ± 0.31 mg vs. 2.02 ± 0.21 mg) and expression levels of collagen II and aggrecan were significantly increased, and the levels of inflammatory factors and the expression levels of TLR4, MyD88, and p-p65 were significantly decreased in IDD rats treated with PU. In vitro: Compared with the IL-1β group, the proliferation activity of IL-1β-treated NPCs and the expression of collagen II and aggrecan were significantly increased, while the apoptosis rate, levels of inflammatory factors, and the expression levels of TLR4, MyD88, and p-p65 were significantly decreased in IL-1β-treated NPCs treated with PU. LPS reversed the biological function changes of IL-1β-treated NPCs induced by PU.Conclusions PU can delay the progression of IDD by inhibiting activation of the TLR4/NF-κB pathway.